Morphological and genetic analysis of Gracilaria sp. cultured in ponds and coastal waters. (November 2019) - Arbit, N I S; Omar, S B A; Soekendarsi, E; Yasir, I; Tresnati, J; Mutmainnah; Tuwo, A
Abstract: Seaweeds of the genus Gracilaria are an important aquaculture commodity, commonly cultured in brackish water ponds as well as in coastal waters. In South Sulawesi, Indonesia, the Gracilaria acultured in ponds has been named G. verrucosa, while Gracilaria cultured in coastal waters has been named G. gigas. Morphologically, these two types of Gracilaria do look different. Detailed examination shows that they appear to have similarities. This study aimed to examine whether these two types of Gracilaria are different species or not. The study used morphological characters and COI mitochondrial gene barcoding to assess the Gracilaria types cultured in ponds and coastal waters. Samples were collected from Ujung Baji Village in Takalar Regency, the main seaweed producing region in South Sulawesi Province, Indonesia. The results indicate that both Gracilaria types have similar genetic characteristics as well as shared morphological characters. Based on these analyses, it is considered that both Gracilaria types cultivated may be strains of the same species.